Effects of Jump on balance and reaction time in women - Picolini, Luana Carvalho (2016)
Introduction: “Jump” exercise has been gaining attention, especially among women. Objective: The aim of this study was to investigate the effects of Jump exercise on the balance and reaction time of women. Methods: Twelve women with a mean age of 22.9 ± 3.31 years participated in the study. They had sixteen-jump exercise sessions with a duration of 60 min. Movements used in all sessions varied changed in direction and steps with a single leg, and bipedal support was applied. Results: Statistically significant differences were observed only in the simple reaction time (t = 6.36, p = 0.000), indicating that Jump exercise can improve simple reaction time. As for the balance and choice reaction time, even though there was an improvement from pre to post tests, the results were not statistically significant. Conclusion: Although there were no statistical differences, choice reaction time and the balance proved to be important capabilities for a more physically active life.